Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2010
DOI: 10.1145/1753326.1753650
|View full text |Cite
|
Sign up to set email alerts
|

Designing patient-centric information displays for hospitals

Abstract: Designing Patient-Centric Information Displays for Hospitals ABSTRACTElectronic medical records are increasingly comprehensive, and this vast repository of information has already contributed to medical efficiency and hospital procedure. However, this information is not typically accessible to patients, who are frequently under-informed and unclear about their own hospital courses. In this paper, we propose a design for in-room, patient-centric information displays, based on iterative design with physicians. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 23 publications
0
69
0
Order By: Relevance
“…Recent work has demonstrated the benefits of computer-based presentation of medical data to hospital patients, through kiosks [5], in-room displays [9] or agents [1]. This work motivates ours, which opens a new approach for automatic content generation for these patient-facing media.…”
Section: Related Workmentioning
confidence: 73%
“…Recent work has demonstrated the benefits of computer-based presentation of medical data to hospital patients, through kiosks [5], in-room displays [9] or agents [1]. This work motivates ours, which opens a new approach for automatic content generation for these patient-facing media.…”
Section: Related Workmentioning
confidence: 73%
“…One line of research addressed gaps in patient knowledge about the care process through the design of displays to deliver timely information. Wilcox et al proposed and piloted a design for large, patient-centric information displays to keep emergency department patients informed about the status of their care using data in the patients electronic record [35], while Pfeifer Vardoulakis and colleagues prototyped mobile displays for a similar purpose [25]. Bickmore et al introduced a bedside mobile kiosk through which an animated virtual nurse agent teaches low-literacy hospital patients about their post discharge care plan [5].…”
Section: Patient-clinician Communication About Electronic Health Recomentioning
confidence: 99%
“…Ong et al [18] presented a literature survey of doctor-patient communication, summarizing the key topics of information exchange, interpersonal relationship building, and shared medical decision making. Wilcox et al [19] proposed a design for patient-centric information displays to deliver useful information to a patient during an emergency room visit, since the patients are frequently under informed. Previous work has also demonstrated that technology can positively impact communication.…”
Section: Public and Patient Educationmentioning
confidence: 99%